NEW MEAT PRODUCTS WITH IMMUNOMODULATORY EFFECT CREATION METHOD - I. V. Kaltovich; O. V. Dymar (Теория и практика переработки мяса)
New meat products with immunomodulatory effect creation method reflecting differential characteristics of technological stages of manufacture of those types of meat products, including issues on the selection of primary and secondary raw materials, guidelines for development of formulations and production technologies, legislative requirements towards its labeling, etc, has been developed for the first time. A list of prospective meat raw materials for the manufacture of products with immunomodulatory effect was established: beef, pork, rabbit meat, broiler chicken meat, turkey, veal, ostrich meat, which have high content of protein (14,3– 21,7%), low content of fat (1,2–16,1%), excluding pork (33,3%), high levels of minimum amino-acid score (90,0–104,0%), protein quality indicator(0,91–1,64), essential amino acid index (1,16-1,25), coefficient of utility of amino acid content (0,72–0,86) and close to optimum fatty acid content, and also contain a great number of vitamins and minerals which play a significant role for immunity improvement. It was determined that the following functional ingredients are recommended to use: amino acids (valine, leucine, isoleucine, methionine, threonine, arginine, tryptophan, lysine, histidin, phenylalanyl), vitamins and provitamins (C,E, beta-carotene, B vitamins(Bc, B12, PP, etc.), P(bioflavonoid complex), H, K), minerals (calcium, magnesium, iron, cuprum, zinc, manganese, selenium), polyunsaturated fatty acids omega-3 and omega-6, pseudo-vitamins (L-carnitin, coenzyme Q10), polysaccharides and peptides naturally occurring(squalen, B-Carotene), ginger, shiitake mushrooms, probiotics and prebiotics, glutathione, indole and lycopienes, bioflavonoids, L-arginine, N-acetylcysteine, gel from seaweed «Lamifaren». The use of the developed meat products with immunomodulatory effect creation method by process engineers of meat processing factories will allow them to form a single scientifically grounded approach during the development, launching into manufacture and organization of industrial manufacture of functional meat products, ensuring the compliance of quality and safety indicators of innovative products with legislative requirements, applied to meat products, taking into account nutritional habits and containing a well-balanced set of functional ingredients with immunomodulatory effect, the consumption of which will promote immunity improvement that will positively affect health promotion.